Impact of organic nutrients on soil health and enzyme activity in soybean (Glycine max) on typic Heplustepts soils in Rajasthan - YADAV, M K; PUROHIT, H S; MEENA, S C; YADAV, S K; SHARMA, S K; JAIN, H K (The Indian Journal of Agricultural Sciences, 2020)
A field experiment entitled, impact of organic nutrients on soil health and enzyme activity in soybean (Glycine max L.) on typic Heplustepts soils in Rajasthan was conducted at Instructional Farm, Rajasthan College of Agriculture, Udaipur during consecutive kharif season of the year 2016 and 2017. The experiment was evaluated in randomized block design (RBD) with three replications. Organic manures (FYM, compost, green leaf manure and vermicompost) were incorporated in treated plots before 15 days of sowing. Variety JS-9560 of soybean was sown as per recommended package of practices. Results showed that organic carbon, available N, P, K and micronutrients, viz. Fe, Zn, Cu and Mn in soil were found maximum at harvest stage of soybean with the application of 100% vermicompost treatment. Enzyme activity dehydrogenase and phosphate activity in soil were significantly influenced through organic nutrient fertilization of 100% vermicompost treatment. Maximum net return of ₹ 60785.07 with benefit cost ratio of 2.9 was obtained with the application of 100% RDF, followed by 100% vermicompost.